2020
DOI: 10.3390/mps3030048
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DNA Extracted from Pediatric Saliva, Gingival Crevicular Fluid and Site-Specific Biofilm Samples

Abstract: (1) Introduction: Due to the non-invasive nature of saliva, many methods have been used to isolate and collect DNA from saliva samples for microbial screening. Many oral microbes also inhabit the oral biofilm, which may represent significantly different microbial constituents that may contribute to oral health and disease, including caries and periodontal disorders. Moreover, the biofilm may vary within the same patient at different sites. Few studies have evaluated the comparison between DNA isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…DNA was isolated from 100 μL of saliva samples and from paper points that were placed into 100 μL of sterile 1X phosphate-buffered saline (PBS) and vortexed to release any bacteria or other microbial constituents. Each sample was then processed using the phenol: chloroform extraction method, as previously described [ 21 , 28 ]. In brief, 300 μL of TriZol was added to each sample and mixed to dissolve microbial membranes and cell walls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA was isolated from 100 μL of saliva samples and from paper points that were placed into 100 μL of sterile 1X phosphate-buffered saline (PBS) and vortexed to release any bacteria or other microbial constituents. Each sample was then processed using the phenol: chloroform extraction method, as previously described [ 21 , 28 ]. In brief, 300 μL of TriZol was added to each sample and mixed to dissolve microbial membranes and cell walls.…”
Section: Methodsmentioning
confidence: 99%
“…Most recently, a series of site-specific sampling studies from this group have revealed differential oral locations for SW distribution among patient samples—a major step towards understanding the potential sites for colonization [ 27 , 28 ]. However, due to the limited number of patient samples available in these initial studies, a larger and more comprehensive microbial screening analysis was the overall objective of this current study.…”
Section: Introductionmentioning
confidence: 99%
“…DNA was extracted from paper points by adding 100 µL of sterile 1X phosphate buffered saline (PBS) to each tube and vortexing the tube to release any collected materials. TRIzol from ThermoFisher (Fair Lawn, NJ, USA) was then added to each tube (300 µL) and the extraction method was completed according to the manufacturer protocol, as previously described [24]. In brief, 200 µL of chloroform was added to each tube and then centrifuged at 12,000× g (relative centrifugal force, RCF) for 15 min at 4 • C. The supernatant was removed and placed into a new micro centrifuge tube with 100 µL of isopropanol to precipitate the DNA.…”
Section: Dna Isolationmentioning
confidence: 99%
“…Due to its non-invasive nature, saliva collection has been used to isolate and collect DNA from saliva samples for microbial screening [15 The original protocol for sample collection involved patients providing up to five mL of unstimulated saliva in sterile saliva tubes from each patient. As noted previously [18], the samples were stored in a freezer ( biomedical safety level 2 (BSL-2) laboratory for the purpose of longevity and analysis of the samples. The saliva samples were provided with random, non-repetitive numbers to remove any patient identification factors from the origin of the samples.…”
Section: Saliva Collectionmentioning
confidence: 99%
“…The DNA in the saliva was isolated using the phenol:chloroform extraction method with Invitrogen (TRIzol reagent) known to isolate high quality DNA/RNA from samples in fluids and tissues, as previously described [18]. analysis, 100 μL of saliva was removed μL of TRIzol reagent was added and mixed of chloroform added to the mixture after five minutes.…”
Section: Dna Isolationmentioning
confidence: 99%